Local finances in France: what place? What challenges? - Emilie Moysan (Prawo Budżetowe Państwa i Samorządu)
The finances of local authorities in France have their origins in the French Revolution of 1789. At that time, local authorities were small and their finances too. Everything has changed from the 1980s. Since then, local finances have been a determining component of our public financial system and are even at the heart of current budgetary and fiscal challenges. They also integrate an efficient management of public funds from which the central government draws its inspiration.